The diagnostic conundrum of late-onset developmental regression in child psychiatry: case series - Shalu Elizabeth Abraham; Sakhardande Kasturi Atmaram; Poornima Khadanga; Nirmalya Mukherjee; Rajendra Kiragasur Madegowda; Harshini Manohar (BJPsych Open)
Background Developmental regression in children, in the absence of neurological damage or trauma, presents a significant diagnostic challenge. The complexity is further compounded when it is associated with psychotic symptoms.